Carbon-bromine bond cleavage – A perspective from bromine and carbon kinetic isotope effects on model debromination reactions. (February 2018) - Manna, Rabindra Nath; Grzybkowska, Anna; Gelman, Faina; Dybala-Defratyka, Agnieszka
Abstract: In this work, we explore the effect of solvent on 13 C and 81 Br kinetic isotope effects (KIEs) during elimination of bromine substituent from brominated organic compounds promoted by hydroxyl anion. In the present study, we investigate HBr elimination from 2-bromoethylbenzene in three different polar media (water, ethanol, and acetonitrile) as well as bromide ion elimination from 1, 2-dibromoethane upon nucleophilic substitution by the hydroxyl ion in aqueous solution using carbon and bromine isotope analysis as mechanistic tools. We reconsider the hypothesis that the magnitude of leaving group halide KIE should visibly depend on the solvent and bond-breaking in a protic solvent should be accompanied by hydrogen bonding which would result in less zero-point energy loss than in an aprotic solvent. Modeling the elimination reaction using the available popular theoretical methods along with different approaches for including environment effects we demonstrate in the presented study no interpretable effect of the solvent on the transition state structure and hence on the theoretically predicted KIEs. The comparison of the magnitudes of carbon and bromine kinetic isotope effects for two different mechanistic pathways (elimination vs substitution) is also discussed. Graphical abstract: Image 1 Highlights: HBr elimination from 2-(bromoethyl)benzene proceeds concertedly. No effect of the solvent on transition state structure and kinetic isotope effect. Reaction coordinate mode changes upon different halogen substitution.